Bioethics and the soft power of sport: a contemporary perspective - Kamenecka-Usova, Marina (Frontiers in Sports and Active Living, 2025)
This article offers a perspective on the political dimensions of bioethics within elite sport, particularly regarding the regulation of performance-enhancing methods. Drawing from historical and contemporary examples, it suggests that bioethical decision-making in sport is often influenced by geopolitical agendas, institutional power relations, and national interests. Focusing on the World Anti-Doping Agency's regulatory process, the article argues that scientific assessments may be shaped or delayed by stakeholder lobbying, soft power strategies, and disparities in global access to biomedical innovation. Rather than providing a comprehensive review, this article reflects the author's viewpoint on how bioethics operates within contested frameworks of legitimacy, equity, and global influence. It concludes that recognizing bioethics as politically embedded is crucial for fostering fairer, more transparent, and globally representative governance in sport.